1972
DOI: 10.1152/ajplegacy.1972.223.1.223
|View full text |Cite
|
Sign up to set email alerts
|

Response of large and small coronary arteries to nitroglycerin, NaNO 2 , and adenosine

Abstract: Response of large and small coronary arteries to nitroglycerin, NaNO2, and adenosine. Am. J. Physiol. 223(l) : 223-228. 1972.-Large (2 mm od) and small (.5 mm od) coronary artery strips were mounted side by side in a muscle bath. KC1 concentration was brought to 35 mM to produce tone and isometric tension was measured. Responses were expressed as the percent of the maximum relaxation caused by calcium-free physiological salt solution. NaNOz and nitroglycerin caused greater relaxation of large vessels than smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(42 citation statements)
references
References 1 publication
(2 reference statements)
7
35
0
Order By: Relevance
“…The degree of arteriolar dilation with 10-5 and 10-6 M adenosine in our study is comparable with previous observations (Wahl and Kuschinsky, 1976; Gregory et aI., 1980;Dacey and Duling, 1982). Berne et al (1974) suggested that smaller pial ar teries dilate more than larger ones, similar to the observation in the heart where smaller arteries are more sensitive than larger vessels to adenosine (Schnarr and Spark, 1972 manner to changes in P aco2' Adenosine, a proposed mediator of CBF, is a potent dilator of pial arteri oles in concentration ranges thought to exist phys iologically.…”
Section: Methodologic Consideration Of the Cranial Window Technique Isupporting
confidence: 93%
“…The degree of arteriolar dilation with 10-5 and 10-6 M adenosine in our study is comparable with previous observations (Wahl and Kuschinsky, 1976; Gregory et aI., 1980;Dacey and Duling, 1982). Berne et al (1974) suggested that smaller pial ar teries dilate more than larger ones, similar to the observation in the heart where smaller arteries are more sensitive than larger vessels to adenosine (Schnarr and Spark, 1972 manner to changes in P aco2' Adenosine, a proposed mediator of CBF, is a potent dilator of pial arteri oles in concentration ranges thought to exist phys iologically.…”
Section: Methodologic Consideration Of the Cranial Window Technique Isupporting
confidence: 93%
“…All patients took sublingual NTG (0.4 mg) for chest pain believed to be caused by transient myocardial ischemia. Seventeen patients were taking long-acting nitrates (Nitrol paste, [4][5][6][7][8][9][10][11][12][13][14][15] inches/day, or isosorbide dinitrate, 30 to 240 mg/day, or both). Ten patients were taking propranolol (80-800 mg/day).…”
Section: Methods Patient Selectionmentioning
confidence: 99%
“…The control period was defined as a symptom-free interval during which the left ventricular pressure and heart rate remained unchanged ( ± 10%) for [10][11][12][13][14][15] minutes. After ECG and pressure changes related to injection of selective coronary contrast material returned to baseline (about 5 minutes), a control 105-mm photospot selective coronary angiogram was filmed using 6 ml of Renografin-76.…”
Section: Control Periodmentioning
confidence: 99%
“…Fam and McGregor (22) and Winbury et al (23) have demonstrated that GTN acts preferentially on the large coronary arteries in in situ stud ies with dogs and suggested that this results in increased blood flow to the ischemic region of the myocardium, and may be related to the anti-anginal effect of the drug. Schnaar and Sparks (17) further studied this possibility by examining the relaxing effect of GTN on the isolated vascular smooth muscle from large (2-mm od) and small (550-tm od) coronary arteries of dogs, and confirmed the in situ work suggesting differences in the responses of the vascular smooth muscle of the large and small coronary arteries to GTN. They also found that adenosine causes greater relaxation of the small vessels than the large ves sels (17), which is in agreement with our in vitro data for adenosine.…”
Section: Discussionmentioning
confidence: 83%
“…The coronary vasorelaxing activity of FK409 was addi tionally examined in the vessels with small (0.3-0.5-mm od) and large (2.0 2.5-mm od) diameters by the method of Schnaar and Sparks (17). Since the responses of large and small vessels to a compound could not be directly compared because the small vessel, having less cross-sec tional area, could not exhibit absolute tension changes as great as those of the large vessel, they were expressed as a percent of vessel relaxation after treatment with papaver ine hydrochloride.…”
Section: Resultsmentioning
confidence: 99%